PROFIL PEMECAHAN MASALAH KONTEKSTUAL MATEMATIKA OLEH SISWA KELOMPOK DASAR - Miftakhur Rizki (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2018)
Abstract Problem solving activity is one of the basic activities for human life. The process of finding solutions to solve problems needs students through education one of them. Mathematical contextual problem solving in this paper is defined as a process in completing a contextual math problem which refers to the four polya problem solving steps: 1) understanding the problem, 2) planning the solution, 3) executing the plan and 4) checking again. Subjects in this study were students of grade V SDN 1 Setono. This research is descriptive qualitative research. The results showed that students' ability in solving contextual problems on average showed good categorized results. Students with moderate and high ability are able to carry out the problem-solving procedures with appropriate stages. For students with low skills there is a need for coaching to improve understanding of learning materials with interesting media and strategies. Keywords: Mathematic, Problem Solving, Student,